New challenges for coastal governance in the Azores: marine clusters - Luz Paramio (2008)
The European Union sustainability policies recently reaffirmed by the Lisbon Treaty, shows the makers concerns regarding the maritime sector. The overall approach proposed by the new European policy instruments aimed at reconciling environmental and economic interests both for the Marine and Coastal Zones. Thus, The Outermost regions of the Europe are highlighted over all documents, as areas of great strategic importance to marine management. In Portugal case, the Azores Archipelago has specific characteristics potency the development of a model of sustainability framed within the objectives of the European Marine Policy. Its marine space covered by the dispersion of its nine islands provides the application of the concepts proposed by the current marine instrumental planning framework. The cluster concept introduction as a development promoter allows proper linkages between various maritime sectors and also integrates the perception of ecological economics. Environmental component integration will manage and enhance ecosystems to ensure protection and conservation of marine environment. This paper seeks to identify the challenges that would emerge in the Azores during the implementation of these marine instrumental planning framework principles, regarding marine sustainability in particular, and its impact on Coastal Governance.